A internacionalização estratégica de estudantes: experiências no ensino superior - Amaral, Carla Cristine Borges do (2020)
The socioeconomic transformation of recent decades, as well as globalization, has created the need for students to pursue a high level education, making internationalization an important strategy for the development of their careers. As a consequence, international students represent a major economic and cultural impact - in 2011 there were 4.3 million international students around the globe, and the estimate for 2025 is that this number will exceed 8 million (OECD, 2016) . From this context, this study aims to analyze what are the main barriers, facilitators and motivators for the internationalization of students. Then, a literature review on Internationalization in Higher Education was developed, with students as the unit of analysis, and in-depth interviews with international students located at different academic levels. The results show that the barriers to internationalization are intrinsic and extrinsic to individuals. The main facilitators of internationalization were the training of networking and access to student resources as such, and personal development and career opportunities as the main motivators. This study brings three main contributions: (i) academic for the theme, (ii) managerial for institutions and (iii) practice for students, especially those at the Master and Doctorate level.